Implementasi Program Sejuta Rumah Melalui Fasilitas Likuiditas Pembiayaan Perumahan (Studi pada PT. Bank Tabungan Negara KCP Banyuwangi) - Ramadhan, Arif (Jurnal Administrasi Publik, 2017)
Implementation of Million Houses Program Through Housing Finance Liquidity Facility. This study discusses the implementation of Million Houses Programme through the Housing Finance Liquidity Facility (FLPP) in Banyuwangi regency. This program aims to provide affordable housing finance for the society. The target group of the program are low income communities (MBR). This research uses Edward III implementation model to analyze the implementation of the Million Houses Programme in Banyuwangi regency. This research uses qualitative research with descriptive approach. The finding revealed that the implementation of the Million Houses Programme has been implemented properly. Some problems occurs in resources and communication aspects, such as the lack of officer in duty and the scope still around the urban area.